2019
DOI: 10.3389/fpsyg.2019.00221
|View full text |Cite
|
Sign up to set email alerts
|

Reading-Induced Shifts in Speech Perception in Dyslexic and Typically Reading Children

Abstract: One of the proposed mechanisms underlying reading difficulties observed in developmental dyslexia is impaired mapping of visual to auditory speech representations. We investigate these mappings in 20 typically reading and 20 children with dyslexia aged 8–10 years using text-based recalibration. In this paradigm, the pairing of visual text and ambiguous speech sounds shifts (recalibrates) the participant’s perception of the ambiguous speech in subsequent auditory-only post-test trials. Recent research in adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 68 publications
(120 reference statements)
1
9
0
Order By: Relevance
“…All children successfully performed the text-based recalibration task, as reflected by the different /aba/ response proportions to the ambiguous post-test sounds following each type of exposure block. However, as in our previous study in 8–10 year-old children, these behavioural recalibration effects did not reach significance in the MRI scanner environment 46 , while children in this age range did show significant text-based recalibration in an offline behavioural study 44 . This discrepancy can likely be attributed to the acoustic noise, and/or altered (visual) attentional focus in MRI environment 47 , 48 .…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…All children successfully performed the text-based recalibration task, as reflected by the different /aba/ response proportions to the ambiguous post-test sounds following each type of exposure block. However, as in our previous study in 8–10 year-old children, these behavioural recalibration effects did not reach significance in the MRI scanner environment 46 , while children in this age range did show significant text-based recalibration in an offline behavioural study 44 . This discrepancy can likely be attributed to the acoustic noise, and/or altered (visual) attentional focus in MRI environment 47 , 48 .…”
Section: Discussionsupporting
confidence: 45%
“…This shift in perception is called recalibration and has previously been reported using lip-read speech 37 , 38 , 40 , spoken word context 39 , 40 and overt speech articulation 45 . Behaviourally, reliable text-based recalibration effects have been observed in 8–10 year old children 44 , where the strength of the recalibration effect was found to be associated with children’s categorical perception of phonemes. Functional MRI responses in typically reading adults have shown that the text-induced perceptual shifts can be decoded from activity patterns in the posterior STC and further involve a network of brain areas associated with audio-visual integration and reading, including visual, parietal and frontal regions 42 .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Behavioral evidence has further suggested an absence of this text-induced perceptual shift in adult dyslexic readers ( Keetels et al, 2018 ) while lip-read information was found to yield similar shifts in dyslexic and fluent readers ( Baart et al, 2012 ; Keetels et al, 2018 ). Surprisingly, 8 year-old dyslexic children instead were found to show comparable text-based recalibration to their typically reading peers ( Romanovska et al, 2019 ), emphasizing the importance of studying audio-visual learning processes across multiple age groups. At the same time, we found different cortical activation patterns accompanying these comparable behavioral text-based recalibration effects in children with and without dyslexia ( Romanovska et al, 2021 ).…”
Section: Investigating Text-speech Sound Learning Mechanismsmentioning
confidence: 95%
“…Another paradigm that enables examining perceptual mechanisms associated with short-term audio-visual learning is phonetic recalibration (also “perceptual learning,” Samuel and Kraljic, 2009 ; Vroomen and Baart., 2012 ). Recalibration refers to a shift in an individual’s perception of ambiguous speech induced by the presentation of disambiguating visual input, such as lip-read speech ( Bertelson et al, 2003 ; Vroomen and Baart., 2012 ), spoken word context ( Norris et al, 2003 ), overt speech articulation ( Scott, 2016 ), or text ( Bonte et al, 2017 ; Keetels et al, 2018 ; Romanovska et al, 2019 ). In the classical paradigm, an ambiguous speech sound, e.g., /a?a/ midway between /aba/ and /ada/ is combined with a disambiguating video of a speaker articulating “aba” or “ada.” The subsequent perception of the ambiguous speech sound in auditory-only trials is temporarily biased in the direction of the video – that is, it will be perceived as /aba/ following an “aba” video and as /ada/ following an “ada” video.…”
Section: Investigating Text-speech Sound Learning Mechanismsmentioning
confidence: 99%